Neurotic personality trait as a predictor in the prognosis of composite restorations: A 24-month clinical follow up study - Sulthan Ibrahim Raja Khan (Nature Portfolio, 2021)
Abstract The role of personality traits in modulating the incidence and progression of medical disease conditions are well documented, however, there is a paucity of information for its effects on dental health conditions and specifically on the prognosis of restorative dental materials. This study aims to evaluate the clinical performance of Micro-hybrid and Nano-ceramic composite restorations among patients with different personality traits. A total of 323 patients, indicated to receive operative treatment at a University Dental College Hospital, were invited to participate in this study. Consenting patients were requested to complete the Big Five Inventory (BFI-44 Item) personality questionnaire and were evaluated by a psychiatrist for categorizing the participants based on their personality traits. Out of the recruited patients, 124 patients falling in to the dominant trait of Agreeableness (n = 62) and Neuroticism (n = 62) were included in the study for further investigation. Next, patients from the Agreeableness (Group A) and the Neuroticism personality trait group (Group N) were randomly divided into two subgroups each—sub group Am (n = 44) and Nm (n = 48) for Micro-hybrid composite restorations and Sub group An (n = 42) and Nn (n = 47) for Nano-ceramic composite restorations. Two trained and calibrated dentists prepared the cavities according to previously published methodology. The restorations were evaluated at baseline (immediately after restoration), 6-months, 12-months and 24-months intervals by two blinded independent dental professionals for anatomical form, secondary caries, color match, retention, marginal adaptation, surface texture, marginal discoloration and post-operative sensitivity. There is no statistically significant difference noted in various parameters of restoration performance between Micro-hybrid composite and Nano-ceramic composite compared among ‘agreeableness’ personality group and among ‘neuroticism’ personality group after controlling the personality trait factor. Higher ‘Neuroticism’ individuals had higher restoration deterioration in color matching and surface texture when compared to higher ‘Agreeableness’ trait individuals. Regression analysis showed no effect of gender or cavity size on the outcome of results. Assessment of personality traits may serve as a useful tool during treatment planning which would aid clinicians in choosing suitable restorative dental material and prosthesis design according to individual patient’s physiological and functional needs, thereby overall improving the quality of treatment provided.